The Economic and Legal Imperatives of Marriage Age Regulation: A Posnerian Analysis of National Productivity and Welfare - Muhidin; Trihastuti S., Tuti; Lutrianto A., Indra; Sujatmiko, Bambang; Santiago, Faisal (JURNAL ILMIAH GEMA PERENCANA, 2026)
The enforcement of Law No. 16 of 2019 Amending the Marriage Law (No. 1 of 1974), which revised Indonesia's minimum marriage age, requires robust complementary policies to unlock its full socio-economic potential. This study analyzes the regulation from a Posnerian law and economics perspective, which posits that legal rules should be evaluated based on their capacity to maximize social benefits and minimize social costs. The research employs qualitative method with a normative legal approach, examining statutory provisions, legal doctrines, and international literature. Our findings indicate that raising the marriage age is a critical intervention for optimizing human capital by extending educational attainment and skill acquisition, particularly for women. This delay directly correlates with increased labor productivity, higher lifetime earnings, and enhanced family welfare, thereby reducing the long-term economic burdens of structural poverty and public health costs associated with early marriage. However, the policy's effectiveness is constrained by persistent cultural resistance and social norms in various Indonesian communities. The analysis reveals that without effective enforcement and socio-legal adaptation strategies, the intended economic benefits remain unrealized. The conclusion is that for the marriage age law to serve as a productive instrument for national development, it must be integrated with widespread public education, targeted economic empowerment programs, and consistent legal enforcement to internalize the negative externalities of child marriage and foster sustainable national welfare.